Conversations with power : what great presidents and prime ministers can teach us about leadership - Till, Brian Michael (New York, NY : Palgrave MacMillan, 2011)
'Fresh out of college and just beginning his work as a syndicated columnist and a researcher at the New America Foundation, Brian Till set out to interview the former world leaders he most admired. He hardly expected to get his foot in the door--much less to have revelatory, insightful conversations with so many of them. Here, he distills their collective wisdom into key lessons for aspiring leaders of the future, including the best ways to handle opposition, public opinion, and the information revolution. With a stunning list of interviewees including Bill Clinton, Jimmy Carter, Ehud Barak, and V{u2863}lav Havel, and Nobel Laureates Mikhail Gorbachev, Pervez Musharraf, FW de Klerk, and Martti Ahtisaari, among many others, these conversations provide an illuminating, entertaining, and uplifting reminder of what is possible when great leaders inspire and the public is engaged'--
Includes index.
Keywords: Heads of state -- Biography; Heads of state -- Interviews; Political leadership; POLITICAL SCIENCE / Essays; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State; BIOGRAPHY & AUTOBIOGRAPHY / Political